Applying Criteria to Examples or Learning by Comparison: Effects on Students' Evaluative Judgment and Performance in Writing - Bouwer, Renske; Lesterhuis, Marije; Bonne, Pieterjan; De Maeyer, Sven (Frontiers in Education, 2018)
In higher education, writing tasks are often accompanied by criteria indicating key aspects of writing quality. Sometimes, these criteria are also illustrated with examples of varying quality. It is, however, not yet clear how students learn from shared criteria and examples. This research aims to investigate the learning effects of two different instructional approaches: applying criteria to examples and comparative judgment. International business students were instructed to write a five-paragraph essay, preceded by a 30-minutes peer assessment in which they evaluated the quality of a range of example essays. Half of the students evaluated the quality of the example essays using a list of teacher-designed criteria (criteria condition; n = 20), the other group evaluated by pairwise comparisons (comparative judgment condition; n = 20). Students were also requested to provide peer feedback. Results show that the instructional approach influenced the kind of aspects students commented on when giving feedback. Students in the comparative judgment condition provided relatively more feedback on higher order aspects such as the content and structure of the text than students in the criteria condition. This was only the case for improvement feedback; for feedback on strengths there were no significant differences. Positive effects of comparative judgment on students’ own writing performance were only moderate and non-significant in this small sample. Although the transfer effects were inconclusive, this study nevertheless shows that comparative judgment can be as powerful as applying criteria to examples. Comparative judgement inherently activates students to engage with exemplars at a higher textual level and enables students to evaluate more example essays by comparison than by criteria. Further research is needed on the long-term and indirect effects of comparative judgment, as it might influence students’ conceptualization of writing, without directly improving their writing performance.